Resposta imune a antígenos de Mycobacterium leprae e apresentação clínica da hanseníase como perspectiva para o desenvolvimento de ferramentas para prognóstico e imunoprofilaxia - Santos, Márcio Bezerra (2017)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae. It is estimated that less than 1% of the individuals infected with M. leprae develop the disease. Several authors suggest that the genetic pattern and variations in the mechanisms of the patient's immune response influence the susceptibility or resistance to disease. The most recent studies have established the role of Th1, Th2 and Treg cell responses in immunopathogenesis of leprosy. However, several mechanisms of the immune response that act in clinical evolution still lack clarification, such as the role of Th17 cells, and the innate immune response. The objective of this study was to evaluate the role of the immune response in the clinical presentation of leprosy and the use of M. leprae recombinant antigens as a perspective for the development of prognostic and immunoprophylaxis tools. To investigate the involvement of immune response in the pathogenesis of leprosy, we analyzed the cytokine profile in lesions, in serum, and peripheral blood mononuclear cells (PBMC) stimulated with M. leprae antigens in leprosy patients and household contactants (HHC). CD4+IL-17+ T cells expressing IL-17A, IFN-γ and IL-10 were evaluated by confocal microscopy in lesions from patients with tuberculoid (TT, n = 09) and lepromatous leprosy (LL, n = 08). Inflammatory cytokines were measured in serum samples from 23 paucibacillary (PB) patients, 28 multibacillary (MB) and 23 HHC, using the Luminex technique. The phenotype of lymphocytes producing IL-17A and IFN-γ was determined by flow cytometry. In addition, PBMC from leprosy patients and HHC were stimulated with crude M. leprae (MLCS) and M. tuberculosis (PPD) and a recombinant antigen of M. leprae (ML2028), and the cytokine profile and the CD4+ and CD8+ multifunctional T cells (producing IFN-γ, IL-2 or TNF-α) of effector and central memory were analyzed. We observed that TT lesions expressed more CD4+IL-17A+ cells than LL. Higher levels of IFN-γ were detected in PB patients, but also in MB patients who presented leprosy reactions (LR) at the time of evaluation (MB LR+). Significantly, higher concentrations of IL-17A and IL-1β were observed in serum from PB than in from MB patients. Ex vivo cell analysis by flow cytometry revealed higher frequency of Th17 cells in TT than LL patients, and it is not high in LL patients with LR. These results indicate that the Th17 cells are associated with an effective inflammatory response that occurs in PB presentation of leprosy but were not associated with the inflammatory response in LR. Th1 response was also associated with PB presentation. However, high levels of IFN-γ were also associated with LR. Multiparameter analyzes by flow cytometry revealed a higher frequency of multifunctional T cells specific for M. leprae antigens in HHC than in leprosy patients, and it might explain the absence of disease in these individuals. These data indicate that these antigens are capable of inducing a more effective immune response and multifunctional T cell memory against M. leprae infection, and open perspectives for the future development of immunoprophylaxis with M. leprae antigens. Additionally, this study suport the attempt to induce a Th1 and Th17 response in individuals at risk of acquiring the disease, even considering this could induce only a partial protection, because it would protect against the most severe MB forms of leprosy, and reduce the disease transmission. This Thesis includes one paper accepted for publication, about the role of Th1 and Th17 cells in subjects with different clinical forms of leprosy, and another paper submitted about the immune response to M. leprae crude and recombinant antigens.